NARASI BUDAYA DAERAH UNTUK PENCIPTAAN BRAND IDENTITY “BALE BUDAYA PARAHYANGAN” DI KAWASAN KOTABARU PARAHYANGAN BANDUNG - Sru Setyohadi; Wegig Murwonugroho; Agung Eko Budiwaspada (Kartala Virtual Studies, 2024)
The reduced interest of the younger generation in arts and local culture is the impact of the era of globalization which has influenced the pattern of cultural life in this country. They prefer foreign culture which they consider to be more modern and classy compared to regional culture which is outdated and outdated. This means that someone who cares about culture established a cultural hall in the Kota Baru Parahyangan Mandiri City area in the Padalarang area of West Java, to facilitate community activities in preserving the nation's culture. Not only for art but also as a place for recreation, education and conservation, but unfortunately the place called "Bale Budaya Parahyangan", is not widely known by the local community due to the lack of information and the absence of a brand identity, this is the main problem. So there is a need for a significant brand identity concept that takes regional cultural narratives as the approach and is based on qualitative research methods and design techniques using the design thinking process, so that it is easier to recognize and understand both the meaning and the visuals.